2015
DOI: 10.1186/s13052-015-0187-6
|View full text |Cite
|
Sign up to set email alerts
|

Each niche has an actor: multiple stem cell niches in the preterm kidney

Abstract: The preterm kidney cannot be simply considered as a kidney small in size: as compared to the adult kidney, the developing organ of the preterm infant is characterized by marked differences regarding the architecture and cell components. At macroscopy, fine linear demarcations indenting the renal surface characterize the fetal and preterm kidney. At microscopy, multiple major architectural changes differentiate the developing kidney from the adult one: a large capsule with a high cellularity; the branching uret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Also, injection of papillary stem cells under the renal capsule led to their incorporation into various tubule segments [4] . Moreover, other niches had been detected in the Bowman′s capsule, the cortical and medullary interstitium, the renal papilla and the hilar regions [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, injection of papillary stem cells under the renal capsule led to their incorporation into various tubule segments [4] . Moreover, other niches had been detected in the Bowman′s capsule, the cortical and medullary interstitium, the renal papilla and the hilar regions [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Also Park et al (2010) described renal stem cell niche but they concluded that the renal capsule is a potential stem cell niche [24] . Moreover Fanni et al (2015) detected stem cell niche in Bowman's capsule, where progenitor cells exist intermingled with parietal epithelial cells [25] .…”
Section: Discussionmentioning
confidence: 99%
“…The nephrogenic zone of a fetal mammalian kidney straddles as a band beyond the organ capsule and shows a width of up to 100 µm depending on species [14]. In histological sections stained by hematoxylin-eosin solution it exhibits a slightly pronounced color profile [15]. For this reason, the nephrogenic zone is termed in single cases 'blue strip'.…”
Section: Coordinates For Orientationmentioning
confidence: 99%